Aluminiumsilikatfasern (Refractory Ceramic Fibres, RCF) [MAK value documentation in German language, 2019]. Issue 3 (1st August 2019) - Hartwig, A.; ,
Abstract: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated aluminium silicate fibres considering all toxicological endpoints. Aluminium silicate fibres cause mesotheliomas and lung tumours in rats and hamsters. In epidemiological studies, cancer risk was not associated with exposure to aluminium silicate fibres. Tumour formation in animals is a result of chronic inflammation; therefore, aluminum silicate fibres are a candidate for Carcinogen Category 4. However, the re‐evaluation showed that a maximum concentration at the workplace (MAK value) cannot be derived and aluminium silicate fibres thus remain classified in Carcinogen Category 2. Aluminium silicate fibres are not taken up via the skin in toxicologically relevant amounts. There are no studies of sensitization.